Type IV congenital pouch colon in male children: Anatomical variations and a proposed new subclassification - Shailesh Solanki (Journal of Indian Association of Pediatric Surgeons, 2020)
Background: Congenital pouch colon (CPC) is a rare variant of anorectal malformation. In male patients, CPC communicates distally with the urogenital tract by a large fistula. The CPC cases which do not fulfill the criteria as mentioned in the classical description are reported along with the pertinent literature review. Materials and Methods: This was a retrospective study from January 2004 to December 2017 of male children with Type IV CPC. We evaluated clinical presentation, primary management, anatomical relationship, previous surgical intervention, definitive management, result, and outcome in terms of continence status on Templeton score. Results: Fifty-one children were included in the study among whom 36 children (Group 1) had a colovesical fistula and 15 children (Group 2) had no communication of the pouch with the genitourinary tract. In Group 2 children, the clinical presentations and management were varied: 4 underwent primary pull-through procedure, whereas 11 underwent staged procedure. Group 2 included three children in whom a narrow and thin-walled anal canal or anal canal with lower rectum was present, which was incorporated during the pull-through procedure. On continence assessment, only one child in Group 1 had “good” continence score compared to four children (three having anal canal) in Group 2. Conclusion: CPC Type IV can present without genitourinary tract communication (fistula), contrary to its emblematic description. Awareness about anatomical variations and adaptation of surgical technique accordingly is vital. The identification of the anal canal with or without the lower part of the rectum (even though apparently narrow and thin walled) and incorporation of this in bowel continuity lead to better outcomes in terms of continence.